PENGARUH TEKNOLOGI INTERNET DALAM MENINGKATKAN PROSES PENGAJARAN GURU DI SD GLOBAL PRESTASI BEKASI - Magdalena Gire Namang; Santoso Setiawan; Esty Purwaningsih (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2018)
Internet technology is no longer just known as assistive devices or entertainment purposes only but has evolved into one of the tools in the learning system. Learning can be done anywhere and anytime. The learning process will not achieve optimal results if not balanced diversity of approaches and methods, both individual and group approach. This means that instead of teacher teaching resources but also other learning resources to meet the educational elements. Teachers in schools in accordance with the functions assigned to optimize the ability of students in the learning process in the classroom. The role of the teacher in question is all matters relating to all aspects including approaches to teaching in schools. But what happened in school today are teachers who tend to simply explain and tell something to the students alone and glued to the existing textbooks. Learning model like that many students is more passive and less likely to feel bored. Therefore, teachers should be able to change the old paradigm by utilizing internet technology in the learning process in the classroom are not only using textbooks.